Comparative outcomes of open and robotic-assisted radical cystectomy in an enhanced recovery programme era. (May 2015) - Pai, Aakash; Nair, Rajesh; Ayres, Benjamin; Tsoi, Hermione; Sooriakumaran, Prasanna; Issa, Rami; Perry, Matthew
Aim: The aim of this study was to determine the added value of robotic surgery for radical cystectomy in the context of an established enhanced recovery programme (ERP). Background: We have previously reported on ERP in open radical cystectomy (ORC) and shown that it is safe and not associated with an increase in complications or readmissions. Further, it is associated with reductions in ICU stay, length of hospital stay and duration of postoperative ileus. The recent introduction of robotic-assisted radical cystectomy (RARC), with its perceived benefit of minimal invasiveness, has led to the question of whether patients who have their radical cystectomy in the environment of ERP would experience an added benefit if the surgery were performed robotically. We implemented the ERP for all patients undergoing radical cystectomy in 2008. In 2010 we started to offer RARC as the first line treatment for all bladder cancer patients with an indication for bladder extirpation. In this study we compare the perioperative results of the last 50 RARC patients with the last 50 ORC. The same ERP protocol was implemented in all patients. Patients and methods: We used our prospectively kept electronic database to identify the last 50 ORC and 50 RARC patients (we excluded the first 10 RARC in our series to reduce learning curve effect). We compared preoperative (age, sex, comorbidity), intraoperative (diversion type, fluid loss, blood transfusion, conversion and number of lymph node dissections (LND)) and post-operative (length of stay LOS, nodal yield and pathological T stage) variables. We also reported on the 30 day complications according to Clavien–Dindo classification. Results: The two groups did not differ significantly in their preoperative variables, number of LND performed and pathological T and N stage. Patients in the RARC arm were more likely to have continent diversion and had significantly less intraoperative fluid loss. LOS and lymph nodal yield was no worse in the RARC cohort in comparison to the ORC patients. The RARC patients had significantly lower transfusion rates and overall 30-day complication rates. Conclusions: We have shown that robotic surgery offers an added value to patients undergoing radical cystectomy for bladder cancer in addition to the benefits gained from enrolling in an ERP. This is likely due to the minimally invasive nature of robotic surgery, and thus an attenuation of its physiological insult, which is the cornerstone of ERP theory.